All Nations Breath of Life: A Randomized Trial of Smoking Cessation for American Indians - Choi, Won S. (Am J Prev Med, 2016)
INTRODUCTION: American Indians have the highest cigarette smoking prevalence of any racial/ethnic group in the U.S. There is currently no effective empirically-based smoking-cessation program for American Indians. The purpose of this study was to determine if a culturally tailored smoking-cessation program, All Nations Breath of Life (ANBL), is more effective than a non-tailored cessation program among American Indian smokers. DESIGN: A multisite RCT was conducted from September 2009 to July 2014; analysis was conducted in 2015. SETTING/PARTICIPANTS: Participants were rural or reservation-based American Indian smokers aged ≥18 years. INTERVENTION: Smokers were group randomized to either the culturally tailored ANBL or non-tailored current best practices (CBP) for a total enrolled sample size of 463 (ANBL, n=243; CBP, n=220). MAIN OUTCOME MEASURES: The primary outcome of interest was salivary cotinine–verified 7-day point prevalence smoking abstinence at 6 months. Results for both responder-only and intent-to-treat analyses for self-reported and cotinine-verified abstinence are presented. RESULTS: Intention-to-treat, imputing all non-responses as smokers, the self-reported point prevalence abstinence rates at 12 weeks were 27.9% in the ANBL arm and 17.4% in the CBP arm (p=0.028). There was a statistically significant difference in self-reported 6-month intent-to-treat point prevalence abstinence rates between ANBL (20.1%) and CBP (12.0%) arms (p=0.029). None of the cotinine-verified results were statistically significant. CONCLUSIONS: The culturally tailored smoking-cessation program ANBL may or may not be an effective program in promoting cessation at 12 weeks and 6 months. Participants in the culturally tailored ANBL program were approximately twice as likely to quit smoking at 6 months compared with the CBP program, using self-reported abstinence.